HUBUNGAN MEAN PLATELET VOLUME DENGAN HbA1C DAN PROFIL LIPID PADA PENDERITA DIABETES MELITUS - Mus, Rosdiana; Camin, Yeremiah Rubin; Noortiningsih, Noortiningsih (JURNAL MEDIA KESEHATAN, 2020)
The prevalence of Diabetes mellitus (DM) from year to year is increasing. DM is characterized by hyperglycemia and glucose intolerance that occurs because the pancreatic gland is not able to produce insulin in an adequate or because the body cannot use insulin produced effectively or both. In patients with DM, atherosclerosis accounted for almost 80% of all deaths. In patients with DM dysfunction occurs from platelets. Platelets play a role in the process of hemostasis and have important roles in atherosclerosis and arterial thrombosis. The average platelet Volume or known as Mean Platelet Volume (MPV) is the marker of function and the activation of platelets. This research aims to see the relationship between MPV and the lipid profile in patients with DM. This research is a cross sectional research on medical record in the Rebo Market District general Hospital with samples of 300 patients. Data is obtained from January 2014 until December 2015. The Data was analyzed by using the help of SPSS 22.0 with double linear regression test methods. The resulting statistical test showed that there was no significant link between the MPV with lipid and pp glucose profiles (P > 0.05) but there was a significant link between the MPV and the fasting glucose (p < 0.05) in the DM sufferer.